Multimodal comprehension in left hemisphere stroke patients - Vigliocco, Gabriella (Cortex, 2020)
Hand gestures, imagistically related to the content of speech, are ubiquitous in face-to-face communication. Here we investigated people with aphasia’s (PWA) processing of speech accompanied by gestures using lesion-symptom mapping. Twenty-nine PWA and 15 matched controls were shown a picture of an object/action and then a video-clip of a speaker producing speech and/or gestures in one of the following combinations: speech-only, gesture-only, congruent speech-gesture, and incongruent speech-gesture. Participants’ task was to indicate, in different blocks, whether the picture and the word matched (speech task), or whether the picture and the gesture matched (gesture task). Multivariate lesion analysis with Support Vector Regression Lesion-Symptom Mapping (SVR-LSM) showed that benefit for congruent speech-gesture was associated with 1) lesioned voxels in anterior fronto-temporal regions including inferior frontal gyrus (IFG), and sparing of posterior temporal cortex and lateral temporal-occipital regions (pTC/LTO) for the speech task, and 2) conversely, lesions to pTC/LTO and sparing of anterior regions for the gesture task. The two tasks did not share overlapping voxels. Costs from incongruent speech-gesture pairings were associated with lesioned voxels in these same anterior (for the speech task) and posterior (for the gesture task) regions, but crucially, also shared voxels in superior temporal gyrus (STG) and middle temporal gyrus (MTG), including the anterior temporal lobe. These results suggest that IFG and pTC/LTO contribute to extracting semantic information from speech and gesture, respectively; however, they are not causally involved in integrating information from the two modalities. In contrast, regions in anterior STG/MTG are associated with performance in both tasks and may thus be critical to speech-gesture integration. These conclusions are further supported by associations between performance in the experimental tasks and performance in tests assessing lexical-semantic processing and gesture recognition.